Pengaruh Dukungan Organisasional Dan Kepuasan Kerja Terhadap Komitmen Organisasional (Studi Pada Koperasi Simpan Pinjam Di Denpasar Utara) - Adhika, I Nyoman Resa; Riana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.04.TAHUN 2016, 2016)
One's commitment to the organization (organizational commitment) is often a very important issue in the world of work. Employees who are emotionally committed to the organization demonstrate higher performance, reduce absenteeism, and likely to quit their jobs reduced. The realization that the higher the employee's performance will depend on organizational commitment. Higher organizational commitment will be affected by the employee job satisfaction and organizational support. The purpose from this research for analyze: (1) the influence of organizational support against job satisfaction, (2) the influence of organizational support against organizational commitment, (3) influence of job satisfaction employee against organizational commitment. Amount of samples in this research as many as 60 people employees on Cooperative Savings and Loans in territory North Denpasar. Engineering samples is Random Sampling and data is were collected with using questionnaire. Technique of analysis which used is Model Analysis of Path. Result of research find that support influential organizations positive against job satisfaction of employees, support influential organizations positive against organizational commitment and job satisfaction employee has positive influence against commitment organizational. Implications from the results of this research is the support organizations need be given maximally in order to enhance the job satisfaction employee on Cooperative Savings and Loans in territory North Denpasar. When satisfaction officer job increased will be able enhance the of organizational commitment of employees on Cooperative Savings and Loans in territory North Denpasar. Keywords : Organizational Support, Job Satisfaction and Organizational Commitment